PENETAPAN KADAR Cadmium (Cd) dan Timbal (Pb) DALAM KERANG HIJAU (Perna Viridis) DARI PERAIRAN KOTA PEKALONGAN - Tri Minarsih (LPPM STIKES Muhammadiyah Kendal, 2019)
Pekalongan is known as a sea food producing city, including shellfish which is one of the additional food ingredients originating from the sea which is favored by Pekalongan people. Shellfish are filter feeder animals that filter food using gills, allowing for the accumulation of metal in the body. The main properties of heavy metals are difficult to degrade, so their existence is naturally difficult to decompose, for example Pb, Cu, Cd and Hg. In this study analyzed the content of Cd and Pb in Green mussels obtained from the waters of Pekalongan City with the Spectrophotometry Visible Method. The results showed that Cd and Pb levels in Green mussels were 0.4644 ppm (SD = 0.0695) and 1.7915 ppm (SD = 0.2894) The Cd content in the shells is still in accordance with the SNI standard 2009, because the Cd content is <1 ppm, while the Pb content in the shells exceeds that of the SNI 2009 standard, because the Pb content is> 1.5 ppm.